GREEN TRANSFORMASIONAL LEADERSHIP TERHADAP PERILAKU KARYAWAN : SYSTEMATIC LITERATURE REVIEW - Shafly, Randika; Jelang Fitri Khothimah, Putri Aryo; Putri Utami, Anindya; Nur Arifah, Reni; Yuliany K, Yetty (JURNAL ILMIAH EDUNOMIKA, 2025)
Companies and individuals recognize the seriousness of environmental issues and support the implementation of sustainable business models. Environmentally friendly behavior among employees, a form of pro-environmental action in the workplace, is crucial for organizations to achieve their conservation goals. To encourage green transformational leadership, it is important to understand the causes and impacts of pro-environmental behavior, as well as the factors that influence these factors. This systematic literature review offers a comprehensive overview of research articles related to green transformational leadership on employee behavior. It draws on numerous articles on the application of green transformational leadership to the performance of conference presenters and participants. The systematic review of the literature in question uses preferred reporting methods for systematic reviews and meta-analyses. Several studies analyze the benefits of green transformational leadership on academic performance. Research in various journals indicates that green transformational leadership has a secret strategy for teaching leadership skills to students through harmonious values and encouraging students to explore the relationships between these individuals and others. Empirical results support the hypothesis that green transformational leadership has an indirect influence on employee behavior through value alignment and a mediating effect that can be mediated by green identity.